1996
DOI: 10.1007/bf02630736
|View full text |Cite
|
Sign up to set email alerts
|

Cyto- and genotoxic effects of coordination complexes of platinum, palladium and rhodium in vitro

Abstract: The growing industrial use of platinum group elements as catalysts, especially in automobile exhaust detoxification (trimetal catalytic converters), is causing increasing occupational and environmental pollution. The cytotoxic and mutagenic properties of industrially used coordination complexes of platinum, palladium and rhodium were investigated using the neutral red cytotoxicity assay on two established cell lines and the Salmonella typhimurium/microsome test system (Ames test). Cytotoxic effects of the plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 28 publications
0
21
0
3
Order By: Relevance
“…The Ames test, which is normally used to evaluate the mutagenic properties of new chemicals and drugs, can be also used to assess the ability of tested compounds to interact with DNA ( Mortelmans and Zeiger, 2000). Bünger et al (1996) have demonstrated that PdCl 2 , K 2 PdCl 4 and (NH 4 ) 2 PdCl 4 were non-mutagenic in the Ames test, contrary to their platinum analogues. Bünger et al (1996) have demonstrated that PdCl 2 , K 2 PdCl 4 and (NH 4 ) 2 PdCl 4 were non-mutagenic in the Ames test, contrary to their platinum analogues.…”
Section: Evaluation Of Mutagenic Activity (Ames Test)mentioning
confidence: 99%
“…The Ames test, which is normally used to evaluate the mutagenic properties of new chemicals and drugs, can be also used to assess the ability of tested compounds to interact with DNA ( Mortelmans and Zeiger, 2000). Bünger et al (1996) have demonstrated that PdCl 2 , K 2 PdCl 4 and (NH 4 ) 2 PdCl 4 were non-mutagenic in the Ames test, contrary to their platinum analogues. Bünger et al (1996) have demonstrated that PdCl 2 , K 2 PdCl 4 and (NH 4 ) 2 PdCl 4 were non-mutagenic in the Ames test, contrary to their platinum analogues.…”
Section: Evaluation Of Mutagenic Activity (Ames Test)mentioning
confidence: 99%
“…• It is possible to overcome the high labile-ligand exchange at Pd-center by designing high thermodynamic stabile and kinetically inert complexes [31]. • Some palladium compounds, contrary to platinum references, showed to be non-mutagenic, in the Ames test, and for this it seems possible to lower potential health risks by applying the palladium-based drugs [32]. • Palladium compounds might materialize a concept of tumor targeting which would result in drugs with other spectrum of activity and lack of cross-resistance as compared with platinum drugs [22].…”
Section: Introductionmentioning
confidence: 99%
“…• The trans-configuration of two leaving groups at square Pd center should not exclude their antiproliferative (or anticancer) activity because recently some very promising antitumor agents were found among the trans-Pt complexes [7,[27][28][29][30][31][32][33]. • It is possible to overcome the high labile-ligand exchange at Pd-center by designing high thermodynamic stabile and kinetically inert complexes [31].…”
Section: Introductionmentioning
confidence: 99%
“…18 Palladium-based drugs, in contrast to platinum references, were non-mutagenic in the Ames test and therefore exhibit a lower potential health risk. 19,20 A number of mixed ligand complexes of phosphines/amines have been reported. 21 The coordination of metal ions to heterocyclic thiones is of current interest because these complexes are used in the synthesis of clinically useful drugs.…”
Section: Introductionmentioning
confidence: 99%